The Impact of Investment Decision and Funding on Financial Performance and Firm Value - Santoso, Hadi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2019)
Managers who are responsible for the management of companies are faced with two important decisions - investment and funding. The right investment decisions and choice of funding sources are important because they affect the company's financial performance. The selection of the types of assets to be invested and the right types of financing sources result in optimal returns for the company. It reflects good company performance and future prospects. In addition, optimal return is a good sign for investors. Companies that perform well experience increase in the value of their firm. This study examined the effect of investment decisions and the selection of appropriate sources of funds on the performance of the company and the consequent impact on the firm value. The study was conducted in two parts. The first part examined the effect of investment decisions on long-term assets with long-term funding on the rate of return and firm value. The second part examined the effect of investment decisions on the company's short-term assets and funding for financial performance and firm value. The case study used in this research is a consumer goods sub-sector company listed on the Indonesia Stock Exchange in the period 2010 to 2017. Path analysis is the data analysis tools that was used. The results of data analysis showed that the asset structure has an effect on financial performance and firm value. The capital structure affects the financial performance but does not affect the firm value of the company. Financial performance was measured by ROI.